The Effect of Cognitive and Metacognitive Learning Strategies in Maharah Qiraah (Speaking Skill) based on Oxford's Strategy Inventory for Language on Students’ Learning Outcomes - Zunairoh, Yuyun (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This study aimed to reveal the use of cognitive and metacognitive strategies by university students in maharah qiraah and to compare such strategies with the success of their learning. Hence, The results can describe the differences in learning outcomes among students using cognitive and metacognitive strategies. This study also sought to get an overview of the cognitive and metacognitive practices in maharah qiraah. As time went by, such practices of learning strategies certainly got some modifications and needed to be reviewed. This research was descriptive-quantitative. The instruments used were 1) a questionnaire adapted from Oxford’s Strategy Inventory for Language Learning; and 2) follow-up interviews to explore the cognitive and metacognitive practices. Conclusion to be drawn was that 62.9% of the students used metacognitive strategies; 17.74% of the students used cognitive strategies; and 19.36% of the students used both cognitive and metacognitive strategies. The questionnaire data were continuously processed by reviewing students’ average scores in maharah qiraah. The students using metacognitive strategies obtained a score of 86.15, while those using cognitive strategies obtained a score of 87.73. Subsequently, thos using both strategies received a score of 85.58. It was concluded that there was no difference in learning outcomes between students who used cognitive, metacognitive, or both strategies. From interview findings, there were several variations in the use of cognitive and metacognitive learning strategies used by students. Cognitive strategies consisted of identifying words and marking them, speed reading to get an outline or main idea, translating, reading repeatedly, using dictionaries and several other sources, analyzing, and reasoning. In the meantime, metacognitive strategies were carried out consciously by focusing attention, organizing alongside planning learning processes, monitoring, and evaluating learning processes. This study has implications to provide an overview of the development of practical forms of cognitive and metacognitive learning strategies so such strategies can be adapted by other language learners.